Design and Development of a Realtime Human Heart Rate Measurement System Using IOT-Based Pulse Sensors - Surja Arafat; Pardede, A M H (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
The heart is one of the important organs that humans have, whose function is to pump blood throughout the body and accommodate it again after cleaning the lungs. Heart rate beats per minute (bpm) is a parameter to show the condition of the heart, and the way to find out the condition of the heart is to know the frequency of the heart rate. This heart rate monitoring tool is designed based on the NodeMCU ESP8266 and a pulse sensor to detect heart rate. This study aims to make it easier to know the heart rate frequency in realtime. A heart rate monitoring tool based on NodeMCU ESP8266 has been designed with a pulse sensor to detect heart rate. Heart rate data from monitoring results will then be sent via a wifi network connection and displayed on the Smartphone.